2019
DOI: 10.3389/fpsyg.2019.01152
|View full text |Cite|
|
Sign up to set email alerts
|

Eliciting ERP Components for Morphosyntactic Agreement Mismatches in Perfectly Grammatical Sentences

Abstract: The present event-related brain potential (ERP) study investigates mechanisms underlying the processing of morphosyntactic information during real-time auditory sentence comprehension in French. Employing an auditory-visual sentence-picture matching paradigm, we investigated two types of anomalies using entirely grammatical auditory stimuli: (i) semantic mismatches between visually presented actions and spoken verbs, and (ii) number mismatches between visually presented agents and corresponding morphosyntactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The absence of a LAN also differs from previous studies (Nichols & Joanisse, 2019;Steinhauer et al, 2009), although some studies focusing on L1-processing have observed an N400, and no LAN, in response to SCVs (Nickels et al, 2014;Zhang et al, 2013). In morphosyntactic studies focusing on agreement, there is currently a debate on whether the LAN is, in fact, an N400 that adopts a frontal, left-lateralized topographic distribution when it is superimposed by a right-posterior P600 (Guajardo & Wicha, 2014; but see discussion in Courteau et al, 2019). Since some LANs have been observed in the absence of a P600 (Hasting & Kotz, 2008), and considering recent studies suggesting that at least some LAN effects are not a product of averaging (Caffarra, Mendoza, & Davidson, 2019), one possibility is that LAN and N400 are not quite distinct but represent a continuum reflecting a mismatch between predicted features and the target, with a topography becoming more N400-like when these features belong to the lexical-semantic domain (Bornkessel-Schlesewsky & Schlesewsky, 2018;Molinaro, Barber, Caffarra, & Carreiras, 2015).…”
Section: Group Effectsmentioning
confidence: 76%
“…The absence of a LAN also differs from previous studies (Nichols & Joanisse, 2019;Steinhauer et al, 2009), although some studies focusing on L1-processing have observed an N400, and no LAN, in response to SCVs (Nickels et al, 2014;Zhang et al, 2013). In morphosyntactic studies focusing on agreement, there is currently a debate on whether the LAN is, in fact, an N400 that adopts a frontal, left-lateralized topographic distribution when it is superimposed by a right-posterior P600 (Guajardo & Wicha, 2014; but see discussion in Courteau et al, 2019). Since some LANs have been observed in the absence of a P600 (Hasting & Kotz, 2008), and considering recent studies suggesting that at least some LAN effects are not a product of averaging (Caffarra, Mendoza, & Davidson, 2019), one possibility is that LAN and N400 are not quite distinct but represent a continuum reflecting a mismatch between predicted features and the target, with a topography becoming more N400-like when these features belong to the lexical-semantic domain (Bornkessel-Schlesewsky & Schlesewsky, 2018;Molinaro, Barber, Caffarra, & Carreiras, 2015).…”
Section: Group Effectsmentioning
confidence: 76%
“…In the introduction, we reviewed arguments that the LAN and N400 are two extremes on a continuum reflecting similar processes, with a topography that can be modulated depending on the input type [41]. In agreement studies, it has been suggested that N400s index a mismatch between word forms (e.g., is / � are agreement mismatches on irregular verbs which are expressed as stems [40,71]) while the LAN reflects mismatching transparent affixes [41]. Transposing this to syntactic categories, (left-lateralized) anterior negativities may be observed when the cues to syntactic category are more grammatical in nature (i.e., provided by inflectional or derivational morphemes), while word stem cues, as we have in our experiment, could lead to more central negativities.…”
Section: 2mentioning
confidence: 99%
“…Thirty-seven French-speaking children and teenagers participated in this study, which is part of a larger research project on neurocognitive processing in DLD 3 (see Courteau et al, 2019). The protocol was approved by the University of Montréal Research Ethics Board for educational and psychology research (CERES-15-070-D).…”
Section: Methods Participantsmentioning
confidence: 99%
“…In addition to clear lexical differences, grammatical ones might also emerge. For instance, Courteau et al (2019) showed that adult speakers of Québec French did not systematically process incorrect omission of subject-verb plural liaison, while Bourget (1987) suggests that this kind of liaison is rarely produced orally in informal Québec French. Speakers would very rarely use the plural feminine thirdperson pronoun elles [ɛlz], "they.fem."…”
Section: Language Assessment Of Québec French-speaking Adolescents Wi...mentioning
confidence: 99%